Examining the moderating role of rational-versus emotional-focused websites: The case of boutique hotels. (April 2014) - Lwin, Michael; Phau, Ian; Huang, Yu-An; Lim, Aaron
This article examines whether emotional or rational advertising appeals are more effective for website hospitality services. Specifically, it considers how attitudes towards websites, service expectations and attitudes towards boutique hotels may influence the two different types of advertising appeals and purchase intention. Results show that websites using emotional appeals tend to show a positive relationship between attitude towards hotels and attitude towards websites and purchase intention. It also indicates that emotional advertisements are better at gaining and retaining interest and attention, and as such can be highly beneficial for small boutique hotels. This article provides several marketing and business policy implications to aid practitioners and strategists in making better decisions.